2014
DOI: 10.3390/ijms151018253
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of Host Cytoskeletal Rearrangements by Shigella Invasins

Abstract: Pathogen-induced reorganization of the host cell cytoskeleton is a common strategy utilized in host cell invasion by many facultative intracellular bacteria, such as Shigella, Listeria, enteroinvasive E. coli and Salmonella. Shigella is an enteroinvasive intracellular pathogen that preferentially infects human epithelial cells and causes bacillary dysentery. Invasion of Shigella into intestinal epithelial cells requires extensive remodeling of the actin cytoskeleton with the aid of pathogenic effector proteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 79 publications
0
13
0
Order By: Relevance
“…Shigella invasion of cells requires the translocation of bacterial effector proteins through the translocon pore into the cytosol. The translocated effectors induce actin rearrangements, which in turn generate membrane ruffles that engulf the bacteria (1719). The effect of cysteine substitutions in IpaC on S.…”
Section: Resultsmentioning
confidence: 99%
“…Shigella invasion of cells requires the translocation of bacterial effector proteins through the translocon pore into the cytosol. The translocated effectors induce actin rearrangements, which in turn generate membrane ruffles that engulf the bacteria (1719). The effect of cysteine substitutions in IpaC on S.…”
Section: Resultsmentioning
confidence: 99%
“…Shigella invasion of cells requires the translocation of bacterial effector proteins through the translocon pore into the cytosol. The translocated effectors induce actin rearrangements, which in turn generate membrane ruffles that engulf the bacteria (17-19). The effect of cysteine substitutions in IpaC on S. flexneri invasion was tested by quantifying the numbers of bacteria internalized during infection of HeLa cells (7).…”
Section: Resultsmentioning
confidence: 99%
“…Results herein and elsewhere (Fisher et al 2014;Vyas et al 2015) suggest that CLso-induced cytoskeletal rearrangement is necessary for systemic psyllid invasion or infection. A similar invasion strategy is used by bacterial pathogens of mammalian (Lee et al 2014) and phytophagous insect (Duret et al 2014;Hogenhout et al 2008) hosts, and also by circulative, propagative plant viruses in their insect hosts (Badillo-Vargas et al 2012;Hogenhout et al 2003;Whitfield et al 2005). Finally, the expression of psyllid-encoded clathrin, profilin, Rac 1, talin, and vinculin gene products previously implicated as Liberibacter-PoP interactors with predicted involvement in systemic invasion (Fisher et al 2014;Vyas et al 2015) is consistent with the observations reported herein during different stages of PoP infection by 'Ca.…”
Section: Discussionmentioning
confidence: 99%